Is the natural feed the better nutritional therapy in patients with severe acquired brain injury? A retrospective study - Adriana Andaloro; Santina Caliri; Francesco Corallo; Placido Bramanti; Carmela Rifici; Maria Cristina De Cola (Clinical Nutrition Open Science, 2021)
SUMMARY: Background: This retrospective study aimed to assess whether the use of natural foods, also in combination with enteral nutrition, improves rehabilitative recovery in patients severe acquired brain injuries. Methods: 40 severe acquired brain injuries patients (75% males, aged 50.2 ± 16.6) were selected. The study population was divided into three groups based on the type of nutrition administered (enteral, oral, and mixed). Mini Nutritional Assessment and Level of Cognitive Functioning scales were used to assess changes from admission to discharge in each group. Multiple logistic regression model was performed to assess the association between the feeding typology and nutritional recovery. Results: At admission, about 97.5% of patients were malnourished. We found significant score changes from baseline to follow-up for both test used and in each subgroup, except for the subgroup that includes patients fed with enteral nutrition. There were significant differences in biochemical indicators, including levels of albumin (p < 0.01) and protein (p < 0.001), compared to baseline and follow-up. Oral nutrition resulted to be a significant predictor for nutritional improvement. Conclusions: Nutrition therapy within a multi-disciplinary team may improve both the hospital care and the recovery in severe acquired brain injuries population. Notably, our findings suggest that natural nutrition is superior to enteral nutrition in improving nutritional outcomes, which should be confirmed by further studies.